Magnetic shape memory microactuators - Kohl, Manfred; Gueltig, Marcel; Pinneker, Victor; Yin, Ruizhi; Wendler, Frank; Krevet, Berthold (Micromachines, 2014)
By introducing smart materials in micro systems technologies, novel smart microactuators and sensors are currently being developed, e.g., for mobile, wearable, and implantable MEMS (Micro-electro-mechanical-system) devices. Magnetic shape memory alloys (MSMAs) are a promising material system as they show multiple coupling effects as well as large, abrupt changes in their physical properties, e.g., of strain and magnetization, due to a first order phase transformation. For the development of MSMA microactuators, considerable efforts are undertaken to fabricate MSMA foils and films showing similar and just as strong effects compared to their bulk counterparts. Novel MEMS-compatible technologies are being developed to enable their micromachining and integration. This review gives an overview of material properties, engineering issues and fabrication technologies. Selected demonstrators are presented illustrating the wide application potential.<br
Keywords: Ferromagnetism; Microsystems technology; Microactuation; Smart materials; Shape memory alloys; Thin films